Campus planning - Dober, Richard P. (New York : Reinhold Publishing Corporation, 1963)
This book is not simply a collection of good photographs of good architecture. Not all the examples are to be emulated.
Section 1. Prospectus -- Section 2. The campus and its parts -- Section 3. Campus plans.
Includes bibliographical references and index.
Keywords: ARCHITECTURAL DESIGNS